Compulsory Admission to Psychiatric Wards–Who Is Admitted, and Who Appeals Against Admission? - Arnold, Benjamin D.; Moeller, Julian; Hochstrasser, Lisa; Schneeberger, Andres R.; Borgwardt, Stefan; Lang, Undine E.; Huber, Christian G. (Frontiers in Psychiatry, 2019)
Background: When persons with a mental illness present a danger to themselves or others, involuntary hospital admission can be used to initiate an immediate inpatient treatment. Often, the patients have the right to appeal against the compulsory admission. These processes are implemented in most mental health care systems, but regulations and legal framework differ widely. In the Swiss canton of Basel-Stadt, a new regulation was implemented in January 2013. While the current literature holds some evidence for factors associated with involuntary admission, knowledge on who uses the right to appeal against admission is sparse. Aims: To examine if specific sociodemographic and clinical characteristics are associated with involuntary admission, and with an appeal against the compulsory admission order. Method: Routine clinical data of all inpatient cases admitted during the period from January 2013 to December 2015 at the Psychiatric University Hospital Basel was extracted. Generalized estimating equation (GEE) analyses were used to examine the association of sociodemographic and clinical characteristics with ‘involuntary admission’ and ‘appeal against compulsory admission order’. Results: Of the 8,917 cases included in the present study, 942 (10.6%) were admitted involuntarily. Of these, 250 (26.5%) lodged an appeal against the compulsory admission order. Compared to cases admitted on a voluntary legal status, cases admitted involuntarily were older, and were admitted more often during the nighttime or weekend. Moreover, involuntarily admitted cases had more often a principal diagnosis of a schizophrenia spectrum disorder. Patients from cases where an appeal was lodged were more often female, had more often Swiss nationality, and were more often diagnosed with schizophrenia spectrum disorder. Conclusion: Despite legal changes, the frequency of involuntary admissions in the observed catchment area seems to be relatively stable across the last twenty years. The percentage of appeals has decreased from 2000 to 2015, and only comparably few patients make use of the possibility to appeal. Better knowledge of the regulations, higher social functioning, and lower insight into illness might be associated with a higher probability of lodging an appeal. Future research should examine if specific patient groups are in need of additional assistance to exert their rights to appeal.